Pengaruh Dewan Komisaris, Dewan Direksi, dan Komite Audit terhadap Profitabilitas : (Studi Empiris pada Perusahaan Sub Sektor Bank yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023) - Winda Oktaviani; Agoestina Mappadang (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study was conducted with the aim of analyzing the board of commissioners, board of directors and audit committee. This study was conducted on Banking Companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The sampling method in this study used the purposive sampling method with a sample of 44 Banking Companies that had met the sample criteria. This study used multiple linear regression analysis techniques and used the SPSS version 22.0 test tool. the results of this study indicate that the variables of the board of commissioners, board of directors, and audit committee do not affect the financial performance of banking companies.